ANALISIS PENGARUH AUGMENTED PRODUCT DAN LOCATION TERHADAP OCCUPANCY RATE HOTEL BINTANG TIGA DI WILAYAH DKI JAKARTA - suyati Djuni Kusuma (Universitas Trisakti, 2002)
The general objectve of this study was to determine the relative variable derived from called as Augmented Prodct on the one hand, and Occupancy Rate of Three Star Hotel on the other hand in DKI Jakarta, Indonesia. Primary data got from apprecials of gues hotel and its managementand apprecial of the researcher for its variable owned by them. Evently, secondary data got and came from Indonesian Association Hotel and Restaurant, Direction General of Toursim, Central Statistical Bureau, Newspapers, Magazine, Brochure and Others. For fomulation acase within this study conceming: